ETIKA KOMUNIKASI ISLAM DALAM PEMANFAATAN SOSIAL MEDIA - Rodiyatul Adawiyah (Universitas Islam Negeri Imam Bonjol Padang, 2025)
Islamic communication ethics in the use of social media encompasses a wide range of principles and guidelines derived from Islamic teachings that aim to increase respect, honesty, and responsibility among users. It promotes a respectful exchange of ideas, protects the privacy and dignity of the individual, and promotes the dissemination of useful knowledge and positive messages. At the heart of Islamic communication ethics is the avoidance of harmful words, gossip, and the spread of lies, which are consistent with the broader Islamic principles of promoting peace, understanding, and community well-being. In addition, this ethic requires caution in the content and interactions shared, which leads users to think about the potential impact of online behavior on themselves and others. The application of Islamic communication ethics in the use of social media not only guides individuals in their personal behavior, but also aims to promote a more respectful, constructive, and harmonious online environment.